Peran dan Fungsi Instansi Yang Melakukan Pengawasan dan Audit Terhadap Perbankan Syariah - Putri Rahma (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
Bank Indonesia and OJK have a supervisory role over sharia banks. However, specifically Islamic banks are also supervised by the National Sharia Council (DSN) and the Sharia Supervisory Board (DPS). Apart from OJK, DSN and DPS, in this case a sharia auditor is also needed who has the task of ensuring the conformity of financial institutions with sharia principles, as well as checking the fairness of financial reports. This research aims to determine the role and function of agencies that carry out supervision and/or audits of Islamic financial institutions in accordance with applicable regulations in Indonesia. This research uses qualitative methods with a normative juridical approach. The data used is secondary data, data obtained by conducting document studies consisting of statutory regulations, scientific studies and journals, books and news articles. The results of this research are that SKAI, Public Accountants, DPS, OJK, and BPK have different roles and functions, but basically have the same goal, namely ensuring that Sharia Financial Institutions in Indonesia run in accordance with the rules and/or statutory provisions. applies in Indonesia and ensures that Sharia Financial Institutions run in accordance with sharia principles.